Strategi Pemasaran Pada Produk Tabungan Simpanan Pelajar (SIMPEL) Di BPRS Bhakti Sumekar Kantor Cabang Madya Pamekasan - Kulsum, Ummu; Rachmawati, Dena Mellia (Mabny: Journal of Sharia Management and Business, 2022)
Technological developments are increasingly sophisticated by shaping the mindset of people who are increasingly advanced and developing, giving rise to competition that has an impact on the banking sector in Indonesia. There is competition that requires financial institutions to compete in providing the best to customers. A bank needs to carry out a marketing strategy because it aims to find out and assess the extent to which the marketing of the products produced can be known by the public so that the products or services offered can be achieved by a company. Two research focuses will be studied. First, to find out the concept of student savings savings (SIMPEL) at BPRS Bhakti Sumekar Pamekasan Madya Branch Office, Second, to find out how the marketing strategy for student savings savings products (SIMPEL) at BPRS Bhakti Sumekar Pamekasan Madya Branch Office. This study uses a qualitative approach with descriptive research type and data sources obtained from primary data and secondary data. The informants are AO/AAO Funding, teachers at schools and students who are SIMPEL savings customers at BPRS Bhakti Sumekar Pamekasan Madya Branch Office. specifically for students or students by using the wadiah yad-dhamanah contract. The characteristics of SIMPEL savings are that it has a very cheap and light initial deposit and the requirements are very easy for students. Second, the marketing strategy used by BPRS Bhakti Sumekar at the Pamekasan Madya Branch Office is Product (Price), Price (Price), Place (Place), Promotion, (Promotion). The product strategy has different characteristics compared to other banks, the price strategy provided has followed the market by providing very cheap prices making it easier for students to save, the strategy chosen is very strategic which is located in the heart of Pamekasan, and the promotion strategy is carried out with carry out socialization to schools by distributing brochures and conducting ball pick-up systems and online promotions via whatsapp and the official website of BPRS Bhakti Sumekar. Keywords: Marketing strategy; Student Savings Savings (SIMPEL)